First‐principles study of f‐orbital‐dependent band topology of topological rare earth hexaborides. Issue 4 (3rd September 2020) - Majid, Abdul; Batool, Amber; Khan, Salah Ud‐Din; Ahmad, Ashfaq
Abstract: The rare earth hexaboride (RE)B6 series of compounds (RE = Ce, Pr, Nd, Pm, Sm, Eu, Gd) was investigated using the first‐principles approach for exploring new topological insulators. The calculated structural, electronic, and magnetic properties of the materials are discussed in detail. To account for better f ‐electron correlation, the Hubbard correction was also tested to correct the Kondo states. The lattice appeared contracted for materials from CeB6 to GdB6, and charge is transferred from RE to boron. The inspection of band structure points to spd hybridization between RE‐ 5d and B‐ 2s, 2p states at Fermi level. The application of spin‐orbit coupling revealed the conversion in the parity, and an odd number of Dirac cones is found at Γ and X points without Kondo mechanism. PrB6, GdB6, and PmB6 revealed a dispersive conic region near the Fermi level at high symmetry points, which enclosed Kramer's degenerate points with surface states of opposite parity. These materials prove to be a strong topological Kondo insulator with an SmB6 ‐like cubic structure without involvement of f‐orbitals in the formation of a Dirac cone. The Hubbard U parameter determined from atomic calculation of RE f‐ orbital, apart from the few cases when f ‐states remain close to the Fermi level, revealed that the band structures are semimetallic in most cases. Abstract : First‐principles calculations were performed to study the structural and electronic properties of a series of SmB6 ‐like bulk rare earth hexaborides with and without the Hubbard approximation. The cubic structures PrB6, GdB6, and PmB6 appeared to be strong topological insulators without the Kondo mechanism. The Hubbard correction revealed that NdB6, SmB6, and PmB6 are Kondo materials due to f‐states on Fermi level.